Arrested development? Sub-Saharan Africa in the stratified world economy 1965–2015. Issue 1 (2nd January 2019) - Grell-Brisk, Marilyn
ABSTRACT: The central concern of this paper is with Sub-Saharan Africa's (SSA) standing in the stratified world economy. Country standings are determined for the period 1965 through 2015, based on the Arrighi and Drangel method of calculating world-system position. We find that the region as a whole remained in the bottom of the global economic hierarchy and was particularly sensitive to macroeconomic-historical changes and pressures. Of note too is the clear link between the SSA countries that are performing well in the semiperiphery of the global economic hierarchy and those with a concentration of natural resources.